KONSEPTUALISASI SPESIFIK BUDAYA PADA WACANA KOLOM PENDIDIKAN DI MEDIA SOSIAL - yulianti, nanda; Mandasari, Yunita; Mabela, Sinta (Lingua, 2022)
The study examined conceptual metaphors related to news on social media and explored the cultural role of creating conceptualization from a cultural perspective. The research analysis technique for the metaphorical identification procedure was inspired by charteris-black's (2004). Based on helpful and discursive cultural approaches to social media data, the study has found metaphorical conceptualization under three high-level conceptual metaphors: news asa threat to human life, news asa threat to human life and the ruling party as kind and good examples eliminate the threat. This metaphorical construction seems to be closely related to the cultural social news that is diverting from virtue, virtue is the essence of human life and rulers will be an example of virtue and live good governance, which stems from Confucian teachings and modern dominant ideology. Some cultural images are also encoded in this research data and have provided a context for the metaphorical concept of the news. The cultural construction above marks a unique news in the lexical, conceptual and cultural aspects. They also had ideological goals to build a positive image for the ruling party. The paper called for more awareness and exploration of cultural concepts. That is, the study discussed is more rooted